Hydrophobic microporous urea formaldehyde foam material and preparation method thereof

By introducing versatile macromolecules into the urea formaldehyde foam material, a self-assembled micro-nano assembly structure is solved, and the problem of urea formaldehyde foam material is not durable, flammable and poor water resistance at high temperatures is achieved, and a strong microporous hydrophobic foam material is achieved. The preparation of the product significantly improves its performance stability.

CN119463271AActive Publication Date: 2025-02-18JIANGSU UNIV OF SCI & TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411643927.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The existing urea-formaldehyde foam materials are not durable, flammable and have poor water resistance at high temperatures, resulting in safety hazards and degradation in building insulation applications.

Method used

By introducing amphiphilic macromolecules, their hydrophilic ends are connected with the urea formaldehyde resin, and the hydrophobic ends are connected with the foaming agent to form a micro-nano assembly structure with self-assembly capability, and regulate the dispersion of the foaming agent and the nucleation of the foaming agent, realizing the nucleation of the foaming agent, thereby achieving the Customization of micropore structures and long-lasting hydrophobic function of foam.

Benefits of technology

The high durability and comprehensive performance of urea formaldehyde foam material have been improved, and a strong microporous hydrophobic foam material has been obtained, which has significantly improved its performance stability in high temperatures and water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463271A_ABST
    Figure CN119463271A_ABST
Patent Text Reader

Abstract

The invention discloses a hydrophobic microporous urea formaldehyde foam material and a preparation method thereof, and belongs to the field of polymer chemical modification. The urea-formaldehyde foam material is prepared from the following raw materials: urea-formaldehyde resin modified by amphiphilic macromolecules, a foaming agent and a curing agent, the amphiphilic macromolecules comprise a hydrophilic end and a hydrophobic end, the hydrophilic end is used for being in reaction connection with the urea-formaldehyde resin, and the hydrophobic end is used for being in reaction connection with the foaming agent. According to the invention, an amphiphilic macromolecular bond is connected into a urea formaldehyde molecular network, so that the amphiphilic macromolecular bond is self-assembled in a urea formaldehyde water-based system to form a micro-nano assembly structure with rich morphology; adjusting the affinity of the foaming agent and the hydrophobic chain link in the assembly structure, inducing the foaming agent to be dispersed in the hydrophobic chain link aggregate of the assembly, and regulating and controlling the foaming and curing process at the same time, so as to limit and fix the nucleation and growth of foam holes in or around the hydrophobic chain link aggregate of the micro-nano assembly, and exert the firm hydrophobic coating effect of the hydrophobic chain link on the foam wall; the urea formaldehyde foam is endowed with a long-acting hydrophobic function, and the construction of a microporous structure is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer chemical modification, and in particular to a hydrophobic microporous urea-formaldehyde foam material and a preparation method thereof. Background Art

[0002] Although the commonly used building insulation foam materials such as polystyrene (EPS) and polyurethane (PU) have excellent comprehensive performance, they are not resistant to high temperatures and are extremely easy to burn. The combustion process produces a large amount of smoke and highly toxic gases, which poses serious safety hazards. Urea-formaldehyde (UF) foam is a thermosetting amino foam material. When it burns, it can produce a large amount of inert gases such as NH3 and CO2, and at the same time form a dense carbonized layer on the surface of the foam to prevent the flame from spreading further. It can reach the flame-retardant level without adding flame retardants. Compared with traditional insulation foam materials such as EPS and PU, UF foam not only has low production costs, but also has the advantages of high temperature resistance, low smoke density, and no molten droplets during combustion, making it an ideal substitute for existing building insulation foam materials. However, the large number of polar groups on the UF molecular chain makes it poor in water resistance and easy to absorb water. After absorbing water, its products gain weight seriously and the thermal insulation performance decreases significantly. Therefore, the large-scale application of building exterior wall thermal insulation products based on UF foam is still a long way to go.

[0003] However, there are few studies on the hydrophobicity and water resistance of urea-formaldehyde resin / foam. In the invention patent with application number 201910048016.2, surface treatment technology is used to introduce long-chain alkyl and siloxane compounds into the surface of urea-formaldehyde foam to construct a hydrophobic and hydrophobic coating, reduce the water absorption rate of urea-formaldehyde foam, and improve the hydrophobic properties of the foam. In the invention patent with application number 201410611186.4, melamine-modified urea-formaldehyde foam is prepared. The introduction of melamine significantly increases the triazine ring structure in the system, increases the hydrolysis activation energy of urea-formaldehyde, and significantly improves the water resistance of the foam material. Other researchers introduced silane coupling agent KH550 during the synthesis of urea-formaldehyde resin, which significantly reduced the number of hydrophilic groups in the system and increased the water resistance of the material. However, the introduction of reactive monomers has a great influence on the molecular structure and synthetic reaction activity of urea-formaldehyde, which in turn affects the mechanical properties of the product; the surface hydrophobic coating is prone to fall off during long-term use, allowing water molecules to gradually diffuse into the pores and destroy the pore structure. In addition, based on the unique molecular structure of urea-formaldehyde and its water-based foaming method, the construction of its microporous structure is extremely challenging, and there is currently no relevant literature report. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a hydrophobic microporous urea-formaldehyde foam material with good durability and excellent comprehensive performance. Another purpose of the present invention is to provide a method for preparing the above-mentioned hydrophobic microporous urea-formaldehyde foam material.

[0005] Technical solution: The hydrophobic microporous urea-formaldehyde foam material described in the present invention comprises the following raw materials in parts by mass: 100 parts of urea-formaldehyde resin modified by amphiphilic macromolecules, 3-18 parts of foaming agents and 1-15 parts of curing agents, wherein the amphiphilic macromolecules include a hydrophilic end and a hydrophobic end, the hydrophilic end includes a hydrophilic chain segment or a hydrophilic group, and the hydrophobic end includes a hydrophobic chain segment or a hydrophobic group; the hydrophilic end is used for reaction and connection with the urea-formaldehyde resin, and the hydrophilic end can participate in the synthesis reaction of urea-formaldehyde, and the hydrophobic end is used for reaction and connection with the foaming agent, and the hydrophobic end has a strong affinity with the foaming agent.

[0006] Preferably, the hydrophobic microporous urea-formaldehyde foam material comprises the following raw materials in parts by mass: 100 parts of urea-formaldehyde resin modified by amphiphilic macromolecules, 8-10 parts of foaming agent and 4-6 parts of curing agent.

[0007] Furthermore, the raw materials of the urea-formaldehyde resin modified by the amphiphilic macromolecules include the following components by weight: 1-15 parts of amphiphilic macromolecules, 100 parts of formaldehyde solution with a mass fraction of 37%, and 26-65 parts of urea.

[0008] Preferably, the raw materials of the urea-formaldehyde resin modified with amphiphilic macromolecules include the following components by weight: 8-12 parts of amphiphilic macromolecules, 100 parts of 37 wt % formaldehyde solution and 40-43 parts of urea.

[0009] Furthermore, the mass ratio of the amphiphilic macromolecule to the foaming agent is 0.6-0.9:1.

[0010] Furthermore, the solubility of the amphiphilic macromolecule in water is greater than 0.1 g / 100 g.

[0011] Furthermore, the hydrophilic end is one or more of a primary amino group, a secondary amino group, an epoxy group, a carbamate group, a hydroxyl group, a ketone group, a phenolic hydroxyl group, an isocyanate group, and an acyl chloride group.

[0012] Furthermore, the hydrophobic end is one or more of a long-chain alkyl chain segment, an organosilicon chain segment, a phenyl group, a halogenated alkyl group, an alkyl group containing an aromatic group, an ester, an ether, an amine, an amide, a polyoxypropylene group, an alkyl group containing a double bond, and a functional fluorine chain segment.

[0013] Preferably, the amphiphilic macromolecule is cetyl polyethylene glycol / polypropylene glycol-10 / 1 dimethylsiloxane (the hydrophilic chain segment is polyethylene glycol / polypropylene glycol containing active hydroxyl groups, and the hydrophobic chain segment is polydimethylsiloxane), a long-chain alkyl monocarboxyl amphiphilic porphyrin (the hydrophilic chain segment is a porphyrin containing an active carboxyl group, and the hydrophobic chain segment is a long-chain alkyl group), or an amino polyether modified silicone oil (the hydrophilic chain segment is a polyether containing an active amino group, and the hydrophobic chain segment is silicone oil).

[0014] Further, the foaming agent is one or more of n-pentane, cyclopentane, n-hexane, 2-methylpentane, 3-methylpentane, 2,3-dimethylbutane, 2,2-dimethylbutane, cyclohexane, cyclopentane, n-heptane, 2-methylhexane, 3-methylhexane, 2,4-dimethylpentane, 2,3-dimethylpentane, 2,2-dimethylpentane, 3,3-dimethylpentane, 3-ethylpentane, 2,2,3-trimethylbutane, n-heptane, 2-methylhexane, 3-methylhexane, and dimethylvinylchlorosilane.

[0015] Preferably, the blowing agent is cyclopentane, 2-methylhexane or 2-methylpentane.

[0016] Furthermore, the curing agent is formic acid.

[0017] The preparation method of the hydrophobic microporous urea-formaldehyde foam material comprises the following steps:

[0018] (1) Preparing a urea-formaldehyde resin modified by an amphiphilic macromolecule: adding an amphiphilic macromolecule to a formaldehyde solution having a mass fraction of 37% to obtain a reaction system, reacting at 30-50° C. for 0.5-1.5 h, adjusting the pH value of the system to 7.5-8.5 after the reaction, adding the first batch of urea, reacting at 50-75° C. for 0.5-1.5 h, adjusting the pH value of the system to 4.5-5.2 after the reaction, reacting for 2-4 h, adding the second batch of urea, continuing the reaction until atomization occurs in the system, adjusting the pH value of the system to 7.5-8.7, and finally adding the third batch of urea. After the reaction for 20-50 min, a urea-formaldehyde resin modified by an amphiphilic macromolecule is obtained;

[0019] (2) The urea-formaldehyde resin liquid modified by the amphiphilic macromolecule, the foaming agent and the curing agent are fully stirred and mixed, and foaming and curing are carried out in a foaming mold to obtain a hydrophobic microporous urea-formaldehyde foam material.

[0020] Furthermore, in step (1), the amount of the first batch of urea accounts for 50-82% of the total urea quality, and the amount of the second batch of urea accounts for 13-37.5% of the total urea quality; the reagent used for pH adjustment is 5-20wt% NaOH solution or 5-20wt% formic acid solution.

[0021] Furthermore, in step (2), the foaming treatment is carried out under the conditions of: foaming at 40-110° C. for 20-90 min.

[0022] Principle of the invention: The present invention connects amphiphilic macromolecules with different hydrophilic and hydrophobic ends to the urea-formaldehyde molecular network, so that they self-assemble in the urea-formaldehyde water-based resin system to form a micro-nano assembly structure with rich morphology; adjusts the affinity of the foaming agent to the hydrophobic end of the assembly, induces the foaming agent to be dispersed in the hydrophobic end aggregate, and at the same time regulates the foaming process to restrict the nucleation and growth of the foam cells and fix them inside or around the aggregate to achieve customization of the microporous structure; at the same time, when the foam cells are dispersed in the hydrophobic chain segment aggregate, the foam wall is firmly coated by the hydrophobic chain segment, giving the urea-formaldehyde foam a long-lasting hydrophobic function, and obtaining a hydrophobic microporous UF foam material.

[0023] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) Different from the traditional microporous construction method, the present invention is based on the controllable self-assembly of amphiphilic macromolecules in the UF water-based resin system, and at the same time regulates the affinity between the foaming agent and the hydrophobic end of the micro-nano assembly and the foaming curing process, so as to restrict and fix the nucleation and growth of the pores inside or around the micro-nano assembly, thereby realizing the construction of a microporous structure. The microporous structure is almost a fully closed-cell structure, which can effectively passivate the crack tip under the action of external force, restrict crack expansion, greatly improve the toughness and strength of the foam, and obtain a tough UF foam material; (2) The present invention cleverly utilizes the hydrophilic and hydrophobic properties of the amphiphilic macromolecules to construct the chemical bonding between the hydrophilic end and the UF molecule, and at the same time exerts the firm hydrophobic coating effect of the hydrophobic end on the foam wall, thereby improving the durable hydrophobic function of the foam and reducing the water absorption rate of the foam. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The cell structure diagram of the hydrophobic microporous urea-formaldehyde foam prepared in Example 1;

[0025] Figure 2 This is a graph showing the water contact angle and water absorption rate of the hydrophobic microporous urea-formaldehyde foam prepared in Example 1. DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with specific embodiments and drawings.

[0027] Example 1: The hydrophobic microporous urea-formaldehyde foam material provided in this example includes the following raw materials in parts by mass: 100 parts of urea-formaldehyde resin modified by amphiphilic macromolecular cetyl polyethylene glycol / polypropylene glycol-10 / 1 dimethylsiloxane (the hydrophilic chain segment is polyethylene glycol / polypropylene glycol containing active hydroxyl groups, and the hydrophobic chain segment is polydimethylsiloxane), 8 parts of cyclopentane as a foaming agent, and 4 parts of formic acid as a curing agent.

[0028] The preparation method of the hydrophobic microporous urea-formaldehyde foam material comprises the following steps:

[0029] (1) 8 parts of cetyl polyethylene glycol / polypropylene glycol-10 / 1 dimethylsiloxane (the hydrophilic chain segment is polyethylene glycol / polypropylene glycol containing active hydroxyl groups, and the hydrophobic chain segment is polydimethylsiloxane) are added to 100 parts of 37% formaldehyde solution, and reacted at 30°C for 0.5h; the pH of the system is adjusted to 7.5 with a 15% NaOH solution, and the first batch of urea (20 parts) is added, and the reaction is carried out at 55°C for 0.5h; then the pH of the system is adjusted to 4.5 with a 5% formic acid solution, and the reaction is carried out for 2.5h; the second batch of urea (15 parts) is added, and the reaction is continued until the system is atomized; then the pH of the system is adjusted to 7.5 with a 15% NaOH solution, and the third batch of urea (5 parts) is added. After reacting for 20min, the material is taken out to obtain a urea-formaldehyde composite water-based resin liquid;

[0030] (2) Add 8 parts of cyclopentane and 4 parts of formic acid to 100 parts of urea-formaldehyde composite water-based resin liquid, stir at high speed for 5 minutes, pour into a foaming mold, and foam at 60° C. for 30 minutes to obtain a hydrophobic microporous urea-formaldehyde foam material.

[0031] Example 2: The hydrophobic microporous urea-formaldehyde foam material provided in this example comprises the following raw materials in parts by mass: 100 parts of urea-formaldehyde resin modified by monocarboxyl amphiphilic porphyrin with amphiphilic macromolecular long-chain alkyl (the hydrophilic segment is porphyrin containing active carboxyl groups, and the hydrophobic segment is a long-chain alkyl), 4 parts of 2-methylhexane as a foaming agent, and 5 parts of formic acid as a curing agent.

[0032] The preparation method of the hydrophobic microporous urea-formaldehyde foam material comprises the following steps:

[0033] (1) Add 5 parts of long-chain alkyl monocarboxyl amphiphilic porphyrin (the hydrophilic chain is a porphyrin containing an active carboxyl group, and the hydrophobic chain is a long-chain alkyl) to 100 parts of 37% formaldehyde solution, and react at 50°C for 1 hour; adjust the system pH to 8.2 with 5% NaOH solution, add the first batch of urea (35 parts), and react at 75°C for 1.5 hours; then adjust the system pH to 5.1 with 10% formic acid solution, and react for 4 hours; add the second batch of urea (6 parts), and continue to react until the system is atomized; then adjust the system pH to 8.5 with 5% NaOH solution, add the third batch of urea (2 parts), and react for 40 minutes before taking out the material to obtain a urea-formaldehyde composite water-based resin liquid;

[0034] (2) Add 4 parts of 2-methylhexane and 5 parts of formic acid to 100 parts of urea-formaldehyde composite water-based resin liquid, stir at high speed for 15 minutes, pour into a foaming mold, and foam at 100° C. for 50 minutes to obtain a hydrophobic microporous urea-formaldehyde foam material.

[0035] Example 3: The hydrophobic microporous urea-formaldehyde foam material provided in this example includes the following raw materials in parts by mass: 100 parts of urea-formaldehyde resin modified by amphiphilic macromolecular amino polyether modified silicone oil (the hydrophilic chain segment is a polyether containing active amino groups, and the hydrophobic chain segment is silicone oil), 10 parts of a foaming agent 2-methylpentane, and 6 parts of a curing agent formic acid.

[0036] The preparation method of the hydrophobic microporous urea-formaldehyde foam material comprises the following steps:

[0037] (1) Add 12 parts of amino polyether modified silicone oil (the hydrophilic chain segment is a polyether containing active amino groups, and the hydrophobic chain segment is silicone oil) to 100 parts of 37% formaldehyde solution, and react at 40°C for 0.8h; adjust the system pH to 8.0 with 10% NaOH solution, add the first batch of urea (30 parts), and react at 60°C for 1h; then adjust the system pH to 4.9 with 15% formic acid solution and react for 3h; add the second batch of urea (10 parts), and continue to react until the system is atomized; then adjust the system pH to 8.5 with 10% NaOH solution, add the third batch of urea (3 parts), react for 30min, and then take out the material to obtain a urea-formaldehyde composite water-based resin liquid;

[0038] (2) Add 10 parts of 2-methylpentane and 6 parts of formic acid to 100 parts of urea-formaldehyde composite water-based resin liquid, stir at high speed for 10 minutes, pour into a foaming mold, and foam at 70° C. for 40 minutes to obtain a hydrophobic microporous urea-formaldehyde foam material.

[0039] Comparative Example 1: The preparation method of the urea-formaldehyde foam material provided in this comparative example is as follows:

[0040] (1) Add 100 parts of 37% formaldehyde solution into a three-necked flask, adjust the pH of the system to 7.6 with 8% NaOH solution, add the first batch of urea (25 parts), and react at 45° C. for 1.5 hours; then adjust the pH of the system to 4.8 with 8% formic acid solution and react for 3.5 hours; add the second batch of urea (15 parts), and continue to react until the system is atomized; then adjust the pH of the system to 7.7 with 8% NaOH solution, add the third batch of urea (6 parts), react for 30 minutes, and then take out the material to obtain urea-formaldehyde water-based resin liquid;

[0041] (2) Add 9 parts of pentane and 5 parts of formic acid to 100 parts of urea-formaldehyde water-based resin liquid, stir at high speed for 10 minutes, pour into a foaming mold, and foam at 65° C. for 60 minutes to obtain a urea-formaldehyde foam material.

[0042] Comparative Example 2: The preparation method of the urea-formaldehyde foam material provided in this comparative example is as follows:

[0043] (1) 7 parts of long-chain alkyl monocarboxyl amphiphilic porphyrin (the hydrophilic chain is a porphyrin containing an active carboxyl group, and the hydrophobic chain is a long-chain alkyl) are added to 100 parts of a 37% formaldehyde solution, and reacted at 35° C. for 1 hour; the pH of the system is adjusted to 8.1 with a 15% NaOH solution, and the first batch of urea (40 parts) is added, and the reaction is carried out at 75° C. for 1.5 hours; then the pH of the system is adjusted to 4.7 with a 15% formic acid solution, and the reaction is carried out for 4 hours; the second batch of urea (10 parts) is added, and the reaction is continued until the system is atomized; then the pH of the system is adjusted to 8.6 with a 15% NaOH solution, and the third batch of urea (2 parts) is added. After reacting for 20 minutes, the material is taken out to obtain a urea-formaldehyde composite water-based resin liquid;

[0044] (2) Add 7 parts of sodium bicarbonate and 4 parts of formic acid to 100 parts of urea-formaldehyde composite water-based resin liquid, stir at high speed for 10 minutes, pour into a foaming mold, and foam at 110° C. for 45 minutes to obtain a urea-formaldehyde composite foam material.

[0045] Comparative Example 3: The preparation method of the urea-formaldehyde foam material provided in this comparative example is as follows:

[0046] (1) Add 30 parts of amino polyether modified silicone oil (the hydrophilic chain segment is a polyether containing active amino groups, and the hydrophobic chain segment is silicone oil) to 100 parts of 37% formaldehyde solution, and react at 40°C for 1.5 hours; adjust the system pH to 8.0 with 10% NaOH solution, add the first batch of urea (35 parts), and react at 65°C for 1.5 hours; then adjust the system pH to 4.7 with 10% formic acid solution, and react for 3.5 hours; add the second batch of urea (8 parts), and continue to react until the system is atomized; then adjust the system pH to 8.3 with 10% NaOH solution, add the third batch of urea (3 parts), and react for 35 minutes before taking out the material to obtain a urea-formaldehyde composite water-based resin liquid;

[0047] (2) Add 10 parts of 2-methylpentane and 7 parts of formic acid to 100 parts of urea-formaldehyde composite water-based resin liquid, stir at high speed for 10 minutes, pour into a foaming mold, and foam at 100° C. for 45 minutes to obtain a urea-formaldehyde composite foam material.

[0048] Comparative Example 4: The difference from Example 1 is that the amount of the foaming agent is 2 parts (the mass ratio of the amphiphilic macromolecule to the foaming agent is 2.7:1).

[0049] Comparative Example 5: The difference from Example 1 is that the amount of foaming agent used is 20 parts (the mass ratio of amphiphilic macromolecule to foaming agent is 0.27:1).

[0050] Comparative Example 6: The difference from Example 1 is that the hydrophilic material polyvinyl alcohol is used to replace the amphiphilic macromolecule.

[0051] Comparative Example 7: The difference from Example 1 is that the hydrophobic material polydimethylsiloxane is used to replace the amphiphilic macromolecule.

[0052] The urea-formaldehyde foaming materials prepared in Examples 1 to 3 and Comparative Examples 1 to 7 were subjected to performance tests. The results are shown in Table 1 below.

[0053] As shown in Table 1 below, the cell size of the urea-formaldehyde foaming material prepared in Example 1 is 5-10 μm, and its electron microscope image is as follows: Figure 1 As shown in the figure, the pores are regular in shape and present a nearly circular closed-cell structure; the water contact angle of the foam and the water absorption rate after immersion in water for 7 days are shown in Figure 2 As shown in the figure, it can be seen that the contact angle is 145.6°, the hydrophobicity is good, and after 7 days of immersion, the water absorption rate increases less. On the 7th day, the water absorption rate is only 10.12%, and the compressive strength is 24.71MPa.

[0054] In Example 2, urea-formaldehyde resin containing a large number of heterocyclic structures is modified by porphyrin, which can effectively block the hydrophilic group and improve the hydrophobicity of urea-formaldehyde foam. Its water contact angle is 147.1°, and the water absorption rate after immersion in water for 7 days is only 9.08%; adding a low-content blowing agent (4 parts, 2-methylhexane) can reduce the foaming ratio of urea-formaldehyde foam and reduce the pore size. The pore size is mainly distributed in a narrow range of 2-8μm, and the compressive strength is increased to 26.98MPa.

[0055] In Example 3, amino polyether modified silicone oil was used to modify urea-formaldehyde resin. After foaming, the water contact angle of the foam was 146.1°, and the water absorption rate after immersion in water for 7 days was 11.01%. When more foaming agent (10 parts of 2-methylpentane) was added, the foaming ratio of urea-formaldehyde foam was larger, and the pore size distribution was in a wide range of 3-11μm, and the compressive strength was 23.09MPa.

[0056] In Comparative Example 1, the urea-formaldehyde resin has not been modified with amphiphilic macromolecules. The measured pore size is larger than that in Example 1, the water contact angle is small, the hydrophobicity is poor, and the compressive strength is only 0.31 MPa. It can be seen that the addition of amphiphilic macromolecules can reduce the pore size of the urea-formaldehyde foaming material and improve its mechanical properties and hydrophobic properties.

[0057] In Comparative Example 2, sodium bicarbonate is used as a urea-formaldehyde resin foaming agent, which has a weak affinity with the hydrophobic chain segments of the long-chain alkyl monocarboxyl amphiphilic porphyrin. The micro-nano assembly structure formed by the amphiphilic macromolecules in the urea-formaldehyde resin liquid cannot effectively regulate the pore size and the hydrophobic properties of the foam. The pore size of the obtained urea-formaldehyde foam is significantly increased compared with that in Example 2, distributed in the range of 20-160 μm, the water contact angle is reduced to 129.7°, and the water absorption rate after immersion in water for 7 days increases to 19.21%. The compressive strength is only 0.89 MPa. It can be seen that the good affinity of the foaming agent with the hydrophobic chain segments of the amphiphilic macromolecules helps to obtain a hydrophobic and high-strength urea-formaldehyde foam material.

[0058] In Comparative Example 3, an excessive amount of amphiphilic macromolecular amino polyether modified silicone oil was added, which could not fully participate in the synthesis reaction of urea-formaldehyde resin and was still dispersed in the urea-formaldehyde resin liquid as free molecules. During the foaming and curing process, a large number of free molecules were "expelled", and macroscopic phase separation occurred in the system. The pore size of the obtained foam was larger than that in Example 1, the water contact angle was reduced, the durable hydrophobic performance was poor, and the compressive strength was reduced to 16.09 MPa. It can be seen that the addition of an appropriate amount of amphiphilic macromolecules can improve the compressive strength and hydrophobic performance of urea-formaldehyde foam.

[0059] In Comparative Example 4, the amount of foaming agent used is only 2 parts, the foaming ratio of urea-formaldehyde is reduced, the pore size is smaller than that of Example 1, the water contact angle is 146.8°, the water absorption rate after immersion in water for 7 days is 10.58%, and the compressive strength is increased to 27.78 MPa. It can be seen that a lower amount of foaming agent can obtain a smaller pore size and higher mechanical strength.

[0060] In Comparative Example 5, the amount of blowing agent used is 20 parts, the foaming ratio of urea-formaldehyde increases sharply, the pore size increases significantly to 150-400 μm compared with Example 1, the water contact angle is 136.3°, the water absorption rate after immersion in water for 7 days increases to 18.11%, and the compressive strength is only 0.34 MPa. It can be seen that excessive blowing agent will mask the regulating effect of the amphiphilic macromolecular assembly on the pore size and the hydrophobic properties of the foam, and it is impossible to obtain a microporous hydrophobic urea-formaldehyde foam.

[0061] In Comparative Example 6, the urea-formaldehyde resin is modified with a hydrophilic material polyvinyl alcohol, and the hydrophilic group content of the system is increased. Compared with Example 1, the water contact angle of the foam is reduced to 116.5°, and the water absorption rate after immersion in water for 7 days increases to 27.08%, showing strong hydrophilicity; at the same time, its pore size is 25-165μm, and the compressive strength is 0.41MPa. It can be seen that the introduction of hydrophilic materials into the urea-formaldehyde system cannot achieve the construction of a microporous structure and the improvement of hydrophobic properties.

[0062] In Comparative Example 7, the hydrophobic material polydimethylsiloxane modified urea-formaldehyde resin cannot be dissolved in water, so it cannot participate in the urea-formaldehyde resin synthesis reaction and is dispersed in the urea-formaldehyde water-based system as free molecules. During the foaming and curing process, the polydimethylsiloxane is gradually "expelled" and migrates to the foam surface to form an uneven hydrophobic coating, which reduces the water contact angle of the foam compared with Example 1. The water absorption rate after immersion in water for 7 days increases to 17.13%, the pore size is 20-170μm, and the compressive strength is 0.38MPa. It can be seen that the introduction of hydrophobic materials into the urea-formaldehyde system can improve its hydrophobic properties to a certain extent, but the microporous reinforced structure cannot be obtained.

[0063] Table 1 Properties of urea-formaldehyde foaming materials obtained from Examples 1 to 3 and Comparative Examples 1 to 7

[0064]

Claims

1. A hydrophobic microporous urea-formaldehyde foam material, characterized in that: The invention comprises the following raw materials in parts by mass: 100 parts of urea-formaldehyde resin modified by amphiphilic macromolecules, 3-18 parts of blowing agents and 1-15 parts of curing agents, wherein the amphiphilic macromolecules comprise a hydrophilic end and a hydrophobic end, the hydrophilic end comprises a hydrophilic chain segment or a hydrophilic group, and the hydrophobic end comprises a hydrophobic chain segment or a hydrophobic group; the hydrophilic end is used for reaction connection with the urea-formaldehyde resin, and the hydrophilic end can participate in the synthesis reaction of urea-formaldehyde, and the hydrophobic end is used for reaction connection with the blowing agent, and the hydrophobic end has a strong affinity with the blowing agent.

2. The hydrophobic microporous urea-formaldehyde foam material according to claim 1, characterized in that: The raw materials of the amphiphilic macromolecule-modified urea-formaldehyde resin include the following components by weight: 1-15 parts of amphiphilic macromolecule, 100 parts of formaldehyde solution with a mass fraction of 37% and 26-65 parts of urea.

3. The hydrophobic microporous urea-formaldehyde foam material according to claim 2, characterized in that: The mass ratio of the amphiphilic macromolecule to the foaming agent is 0.6-0.9:1, and the solubility of the amphiphilic macromolecule in water is greater than 0.1g / 100g.

4. The hydrophobic microporous urea-formaldehyde foam material according to claim 1, characterized in that: The hydrophilic end is one or more of a primary amino group, a secondary amino group, an epoxy group, a carbamate group, a hydroxyl group, a ketone group, a phenolic hydroxyl group, an isocyanate group, and an acyl chloride group.

5. The hydrophobic microporous urea-formaldehyde foam material according to claim 1, characterized in that: The hydrophobic end is one or more of a long-chain alkyl chain segment, an organosilicon chain segment, a phenyl group, a halogenated alkyl group, an alkyl group containing an aromatic group, an ester, an ether, an amine, an amide, a polyoxypropylene group, an alkyl group containing a double bond, and a functional fluorine chain segment.

6. The hydrophobic microporous urea-formaldehyde foam material according to claim 1, characterized in that: The foaming agent is one or more of n-pentane, cyclopentane, n-hexane, 2-methylpentane, 3-methylpentane, 2,3-dimethylbutane, 2,2-dimethylbutane, cyclohexane, cyclopentane, n-heptane, 2-methylhexane, 3-methylhexane, 2,4-dimethylpentane, 2,3-dimethylpentane, 2,2-dimethylpentane, 3,3-dimethylpentane, 3-ethylpentane, 2,2,3-trimethylbutane, n-heptane, 2-methylhexane, 3-methylhexane, and dimethylvinylchlorosilane.

7. The hydrophobic microporous urea-formaldehyde foam material according to claim 1, characterized in that: The curing agent is formic acid.

8. A method for preparing the hydrophobic microporous urea-formaldehyde foam material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Preparation of urea-formaldehyde resin modified by amphiphilic macromolecules: adding amphiphilic macromolecules to a 37 wt % formaldehyde solution, reacting at 30-50° C. for 0.5-1.5 h, adjusting the pH value of the system to 7.5-8.5 after the reaction, adding the first batch of urea, reacting at 50-75° C. for 0.5-1.5 h, adjusting the pH value of the system to 4.5-5.2 after the reaction, reacting for 2-4 h, adding the second batch of urea, continuing the reaction until atomization occurs in the system, adjusting the pH of the system to 7.5-8.7, finally adding the third batch of urea, and reacting for 20-50 min to obtain urea-formaldehyde resin modified by amphiphilic macromolecules; (2) The urea-formaldehyde resin liquid modified by the amphiphilic macromolecule, the foaming agent and the curing agent are fully stirred and mixed, and foaming and curing are carried out in a foaming mold to obtain a hydrophobic microporous urea-formaldehyde foam material.

9. The preparation method according to claim 8, characterized in that: In step (1), the amount of the first batch of urea accounts for 50-82% of the total urea quality, and the amount of the second batch of urea accounts for 13-37.5% of the total urea quality; the reagent used for pH adjustment is 5-20wt% NaOH solution or 5-20wt% formic acid solution.

10. The preparation method according to claim 8, characterized in that: In step (2), the foaming treatment conditions are: foaming at 40-110° C. for 20-90 min.

Citation Information

Patent Citations

  • High-toughness and water-resistant modified melamine urea-formaldehyde resin

    CN104387542A

  • Ultralow-water absorption urea formaldehyde foam material and preparation method thereof

    CN109705393A

  • Method for preparing urea formaldehyde foam powder for plant culture medium through one-step method

    CN104725647A

  • Strength / toughness-modified urea formaldehyde resin foam thermal-insulation material and preparation method thereof

    CN105440575A

  • Urea resin foam material prepared by microwave foaming and preparation method of urea resin foam material

    CN105860433A